Membrane targeted horseradish peroxidase as a marker for correlative fluorescence and electron microscopy studies - Li, Jianli; Wang, Yue; Chiu, Shu-Ling; Cline, Hollis (Frontiers in Neural Circuits, 2010)
Synaptic dynamics and reorganization are fundamental features of synaptic plasticity both during synaptic circuit development and in the mature CNS underlying learning, memory, and experience-dependent circuit rearrangements. Combining in vivo time-lapse fluorescence imaging and retrospective electron microscopic analysis provides a powerful technique to decipher the rules governing dynamics of neuronal structure and synaptic connections. Here we have generated a membrane-targeted horseradish peroxidase that allows identification of transfected cells without obscuring the intracellular ultrastructure or organelles and in particular allows identification of synaptic sites using electron microscopy. The expression of mHRP does not affect dendritic arbor growth or dynamics of transfected neurons. Co-expression of EGFP and mHRP was used to study neuronal morphology at both the light and electron microscopic levels. mHRP expression greatly facilitates 3D reconstruction based on serial EM sections. We expect this reagent will be valuable for studying the mechanisms that guide construction of neuronal networks.